KORELASI PENGARUH FAKTOR EFIKASI DIRI DAN MANAJEMEN DIRI TERHADAP MOTIVASI BERPRESTASI PADA MAHASISWA PENDIDIKAN KIMIA UNVERSITAS BENGKULU - Hermansyah Amir (Manajer Pendididikan, 2016)
The purposes of this study were to analyze using correlational techniques about relationship between self-efficacy and self-management factor on achievement motivation ofChemistry students at Teacher Training and Education Faculty from University of Bengkulu. Respondent population is 140 , and the samples are 104 students, where primary data wasanalyzed with SPPS 16. The results of the study generally indicated that there was a significant and linear effect , partially or together from effect self-efficacy and self-management onachievement motivation of students, which the aspects of self-management was had a greater influence than the aspects of self-efficacy on achievement motivation possessed by the student where all the three aspects are linked and related to each otherKeywords: self-efficacy, self-management, achievement motivation